Branched‐chain amino acid supplementation impairs insulin sensitivity and promotes lipogenesis during exercise in diet‐induced obese mice. Issue 6 (31st March 2022) - Zhang, Hongsong; Xiang, Li; Huo, Mingyu; Wu, Yalan; Yu, Mingyang; Lau, Chi Wai; Tian, Danyang; Gou, Lingshan; Huang, Yuhong; Luo, Jiang‐Yun; Wang, Li; Song, Wencong; et al.
Abstract: Objective: Branched‐chain amino acids (BCAAs) are popular dietary supplements for exercise. However, increased BCAA levels positively correlate with obesity and diabetes. The metabolic impact of BCAA supplementation on insulin sensitivity during exercise is less understood. Methods: Male C57BL/6 mice were fed for 12 weeks with a high‐fat diet, normal chow diet, or BCAA‐restricted high‐fat diet. They were subjected to running exercise with or without BCAA treatment for another 12 weeks. Results: Exercise reduced body weight, improved insulin sensitivity, lowered BCAAs in plasma, and inhibited the upregulation of BCAAs and metabolites caused by BCAA supplementation in the subcutaneous white adipose tissue (sWAT) of obese mice. BCAA supplementation reversed insulin sensitivity ameliorated by exercise. The phosphorylation of protein kinase B (Ser473 and Ser474) was decreased by BCAAs in the sWAT of obese mice. However, BCAA supplementation had no such effects in lean mice. BCAAs also increased the expression of fatty acid synthase and other lipogenesis genes in the sWAT of exercised obese mice. BCAA restriction had no effect on body weight and insulin sensitivity in obese mice. Conclusions: BCAA supplementation impaired the beneficial effect of exercise on glycolipid metabolism in obese but not lean mice. Caution should be taken regarding the use of BCAAs for individuals with obesity who exercise. Abstract : Exercise lowered BCAAs in plasma of HFD‐induced obese mice. BCAA supplementation impaired insulin sensitivity, decreased the phosphorylation of AKT (Ser473 and Ser474) and increased the expression of fatty acid synthase and other lipogenesis genes in white adipose tissue of exercised obese mice. However, BCAA supplementation had no such effects in lean mice. BCAA restriction had no effects on body weight and insulin sensitivity in obese mice.